2020
DOI: 10.1002/jqs.3250
|View full text |Cite
|
Sign up to set email alerts
|

Holocene records of eolian dust deposition from high‐elevation lakes in the Uinta Mountains, Utah, USA

Abstract: Radiocarbon-dated sediment cores from subalpine lakes were used to investigate post-glacial dust deposition in the Uinta Mountains (Utah, USA). Lake sediments were geochemically characterized with ICP-OES, ICP-MS and XRF core scanning. Collections from passive samplers constrain the properties of modern dust, and samples of regolith constrain properties of the local material within the watershed. Ca and Eu are more abundant in dust, whereas Ti and Zr are more abundant in local regolith. As a result, the Ca/Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Statistical analysis reveals that the average amount of extractable Ca in the soils is strongly and positively correlated with the average amount of mineral Ca in the dust, and base saturation in these soils is dominated by Ca (Table 2). As noted above, ratios of elemental abundance in dust/rock and soil/rock reveal that Ca content is greatly elevated in the dust, an observation corroborated by previous work (Munroe et al, 2021a). The wet technique used in this study to remove dust from the collectors might dissolve fine-grained calcite, making it difficult to assess whether calcite is present in the dust, as reported in previous studies (Litaor, 1987).…”
Section: Dust Influence On Pedogenesissupporting
confidence: 84%
See 1 more Smart Citation
“…Statistical analysis reveals that the average amount of extractable Ca in the soils is strongly and positively correlated with the average amount of mineral Ca in the dust, and base saturation in these soils is dominated by Ca (Table 2). As noted above, ratios of elemental abundance in dust/rock and soil/rock reveal that Ca content is greatly elevated in the dust, an observation corroborated by previous work (Munroe et al, 2021a). The wet technique used in this study to remove dust from the collectors might dissolve fine-grained calcite, making it difficult to assess whether calcite is present in the dust, as reported in previous studies (Litaor, 1987).…”
Section: Dust Influence On Pedogenesissupporting
confidence: 84%
“…The primary implication of this conclusion is that future changes in dust flux will have corresponding effects on future soil formation in the mountain CZ. Studies utilizing lake sediment archives have demonstrated that dust fluxes to parts of the Rocky Mountains have changed during the Holocene, likely in response to climatic factors (Arcusa et al, 2020;Routson et al, 2016Routson et al, , 2019Munroe et al, 2021a), so dust flux should not be expected to be invariant. This realization is concerning for two reasons.…”
Section: Discussionmentioning
confidence: 99%